A REVIEW STUDY ON THE EFFECT OF CONFUSION WITH ITS ROLE OF CLARITY ON THE PERFORMANCE OF COLLEGE STUDENT IN HIGHER EDUCATION - Saha, Jhuma; Swarnkar, Naveen Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article is based on the effect of confusion along with its role in clarity on the college students’ study. A SWOT analysis provides insights into its strengths, weaknesses, opportunities, and threats associated with confusion that affect the performance of students in higher education. The role of clarity played a creative in terms of finding solution for proposed problem, but lack of clue or cooperative or collaborative excretion turned it into confusion that disclosed by the moderator or teacher or tutor may be turned into frustration or boredom, if the confusion couldn’t be resolved on time or avoid it or pass it on future, which fragmented the major distractions on student’s study in higher education. Long-term suffering from confusion may indeed turn into boredom, but it may also be helpful, when it, monitored constructively, that can make the learner creative and beneficial for students (D’Mello et al., 2014). Confusion and clarity are both inseparable from the learning of students in higher education, but the teacher, environment, and communication pattern play a key role in enhancing engagement, improving the retention of concepts and learning, positive and inclusive class climate, and encouraging collaborative learning. This article concludes that the subject provides its dependable and independent nature of confusion as well as clarity that affects the student’s performance in higher education.